Continuous flow hydrothermal synthesis of zeolite LTA in intensified reactor. Experimental and multiphysics CFD modeling approach - Ahmad, Sher; Mustapha, Lilia Ben; Calvo, Sébastien; Collignon, François; Fernandes, Antony E.; Toye, Dominique (Chemical engineering and processing, 2023)
•Development of continuous flow intensified reactor for the zeolite LTA.•High quality zeolite LTA crystals were obtained in short residence time.•CFD and population balance models were coupled to closely simulate the process.•Effect of key parameters were studied by simulation of developed model.•The simulations allowed to propose process optimization and scale up. Zeolites are conventionally synthesized in batch-wise hydrothermal processes that usually take several hours or days to complete. In current research work, continuous flow process is developed on pilot scale for the hydrothermal synthesis of zeolite LTA. The pilot reactor was able to produce highly crystalline zeolite nanoparticles without any clogging, which often encounters for particle flow in tubular reactors. Steady-state zeolite production rates of 55–80 g⋅h −1 (dry basis) were achieved with a residence time below 10 min, with corresponding space time yields (STY) between ca. 700 and 1100 g⋅L −1⋅h −1. A couple CFD model with a population balance model was developed to investigate the continuous flow hydrothermal process. The average particle size obtained from the model was in good agreement with the experimental data. The model was further applied to study the effects of critical parameters, such as temperature and flow rate, to highlight potential process optimization directions. [Display omitted]